2017
DOI: 10.1289/ehp575
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Health Effects of Ambient Particulate Matter Estimated Using Ground-Based versus Remote Sensing Exposure Estimates

Abstract: Background:Remote sensing (RS) is increasingly used for exposure assessment in epidemiological and burden of disease studies, including those investigating whether chronic exposure to ambient fine particulate matter (PM2.5) is associated with mortality.Objectives:We compared relative risk estimates of mortality from diseases of the circulatory system for PM2.5 modeled from RS with that for PM2.5 modeled using ground-level information.Methods:We geocoded the baseline residence of 668,629 American Cancer Society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 41 publications
2
90
0
Order By: Relevance
“…A modification to the ACS coefficient of around 30% to 50% for total personal exposure is broadly consistent with previously published evidence suggesting increased coefficients for personal exposure in time-series studies [37,38]. Similarly, studies adjusting coefficients for exposure measurement error using regression calibration techniques have tended to suggest that central monitoring sites generally provide a reasonable representation of overall personal exposures [39][40][41]. However, regression calibration requires detailed information on personal exposures (for instance, based on personal monitoring or remotely sensed data), which commonly does not account for indoor exposures.…”
Section: Discussionsupporting
confidence: 86%
“…A modification to the ACS coefficient of around 30% to 50% for total personal exposure is broadly consistent with previously published evidence suggesting increased coefficients for personal exposure in time-series studies [37,38]. Similarly, studies adjusting coefficients for exposure measurement error using regression calibration techniques have tended to suggest that central monitoring sites generally provide a reasonable representation of overall personal exposures [39][40][41]. However, regression calibration requires detailed information on personal exposures (for instance, based on personal monitoring or remotely sensed data), which commonly does not account for indoor exposures.…”
Section: Discussionsupporting
confidence: 86%
“…However, previous studies are mostly based on single model for the PM 2.5 exposure estimate, which bring much uncertainty. To better express modeling estimate uncertainty, the multi-model method has been applied in several studies especially studies on climate and health, which can be applied in the PM 2.5 exposure estimates (Kinney et al, 2008; Jerrett et al, 2017; Silva et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…However, limitations in using satellite AOD to provide adequate spatial variability in PM concentrations for health effects studies have been noted [49]. A recent examination of several exposure models found that health effects estimated based on models integrating ground-based information and satellite AOD to produce PM 2.5 estimates at a 30 m resolution were larger and had smaller standard errors [50]. Thus, a hybrid approach incorporating information on spatial gradients from roads is possibly the best approach to capture subgrid-scale gradients in satellite observations, particularly when estimating PM exposures that are also temporally resolved.…”
Section: Discussionmentioning
confidence: 99%